Biomaterials and Meniscal Lesions: Current Concepts and Future Perspective - Michele D. M. Lombardo; Laura Mangiavini; Giuseppe M. Peretti (Pharmaceutics, 2021)
Menisci are crucial structures for knee homeostasis. After a meniscal lesion, the golden rule, now, is to save as much meniscus as possible; only the meniscus tissue that is identified as unrepairable should be excised, and meniscal sutures find more and more indications. Several different methods have been proposed to improve meniscal healing. They include very basic techniques, such as needling, abrasion, trephination and gluing, or more complex methods, such as synovial flaps, meniscal wrapping or the application of fibrin clots. Basic research of meniscal substitutes has also become very active in the last decades. The aim of this literature review is to analyze possible therapeutic and surgical options that go beyond traditional meniscal surgery: from scaffolds, which are made of different kind of polymers, such as natural, synthetic or hydrogel components, to new technologies, such as 3-D printing construct or hybrid biomaterials made of scaffolds and specific cells. These recent advances show that there is great interest in the development of new materials for meniscal reconstruction and that, with the development of new biomaterials, there will be the possibility of better management of meniscal injuries